3 - SOUTHERN TUSCANY - C - EASTERN SECTOR OF THE VOLTERRA BASIN - Sandrelli, Fabio (Ofioliti, 2007)
The geological setting of Southern Tuscany, where the Volterra Basin is located, is due to two different tectonic phases. The first one, compressional, is linked to the convergence and collision between the Adriatic Microplate and the European Plate and occurred from the Late Cretaceous to the Early Miocene. The second one is consequence of the extensional tectonic regime active since the Early-Middle Miocene (Carmignani and Kligfield, 1990; Jolivet et al., 1990; Bertini et al., 1992; Carmignani et al., 1994; 1995; Elter and Sandrelli, 1995a; Baldi et al., 1995; Dal Mayer et al., 1996). According to Elter and Sandrelli (1995a; 1995b), the extensional phase included two main events. During the first one, late Burdigalian to early Tortonian in age, there was a rapid uplift of the lithosphere, thickened during both the Alpine and Apenninic orogeneses. The lithosphere never reached the temperature necessary to generate calc-alkaline magmas(600°-650°, Sonder et. al., 1987). This event, was accompanied by “II phase folds” with both east and west vergence, by the emplacement of the Cretaceous Ligurian Units directly on the Triassic evaporites (“Serie ridotta”: Signorini, 1949; Trevisan, 1955; Giannini et al., 1971; Bertini et al., 1992; Decandia et al., 1993) and by the deposition of the Epiligurian Units.During the second extensional event, which started in the late Tortonian, a “thermal re-equilibration” associated to generation of anatectic magmas initiated in a thinned continental crust characterized by a high thermal flow (Table 1 in Elter and Sandrelli, 1995a). The extensional regime led also to the formation of graben and half-graben basins where thick sedimentary successions were deposited. These basins are laterally separated by WSW-ESE transverse lineaments (transfer zones Fig. 1). A different hypothesis on the geodynamic evolution of Southern Tuscany, considers that the first compressional phase acted until the end of the Neogene. In such a case, the sedimentary basins of western Tuscany would have formed as piggy-back or thrust-top basins (Bonini et al., 1994; Boccaletti et al., 1994; Bonini and Moratti, 1995; Boccaletti et al., 1997).During the field trip, we will visit the Volterra Basin between Spicchiaiola and Pignano. This area is particularly important because it lies on the western margin of the Middle Tuscany Ridge and recorded most of the depositional events which occurred in Southern Tuscany from Late Miocene to Pliocene. The four stops will illustrate some of the relationships between tectonics and sedimentation:Stop 1 - Transition from Turolian (upper Tortonian) lacustrine deposits to lower Messinian marine deposits in distal areas of the basin. A transgression affected different formations, highlighting discontinuities and disconformities.Stop 2 - Gypsum deposits formed during the salinity crisis which affected the Mediterranean Sea at the end of early Messinian. A debris flow interrupts the continuity of these deposits, suggesting synsedimentary tectonic activity.Stop 3 - Limestone deposits tilted down near a fault which formed before the deposition of Lower Pliocene marine sediments. This fact documents activity of the border fault between Early Pliocene and late Messinian. This portion of the basin was uplifted during late Messinian and subsided again during Early Pliocene.Stop 4 - The marine deposits of the Early-Middle Pliocene, very well developed in the Mazzolla-Volterra area, where they reach a thickness of about 1200 m. In the western area of Spicchiaiola-Pignano the Pliocene succession is, instead, thin and discontinuous. This difference in thickness is due to a synsedimentary normal fault.